Review: A review on classical and atypical scrapie in caprine: Prion protein gene polymorphisms and their role in the disease. (25th April 2016) - Curcio, L.; Sebastiani, C.; Di Lorenzo, P.; Lasagna, E.; Biagetti, M.
Abstract : Scrapie is a naturally occurring transmissible spongiform encephalopathy in sheep and goat. It has been known for 250 years and is characterised by the accumulation of an abnormal isoform of a host-encoded prion protein that leads to progressive neurodegeneration and death. Scrapie is recognised in two forms, classical and atypical scrapie. The susceptibility to both types of scrapie is influenced by polymorphisms of the prion protein gene ( PRNP ). Sheep susceptibility or resistance to classical scrapie is strongly regulated by the polymorphisms at codons 136, 154 and 171 of the PRNP . The genetic role in atypical scrapie in sheep has been defined by polymorphisms at codons 141, 154 and 171, which are associated with different degrees of risk in the occurrence of the ovine disease. Progress has been achieved in the prevention of scrapie in sheep due to efficient genetic breeding programmes based on eradication and control of the disease. In Europe, the success of these programmes has been verified by applying eradication and genetic selection plans. In general terms, the ovine selection plans aim to eliminate and reduce the susceptible allele and to enrich the resistant allele ARR. During outbreaks all susceptible animals are slaughtered, only ARR/ARR resistant rams and sheep and semi-resistant females are preserved. In the occurrence of scrapie positive goats a complete cull of the flock (stamping out) is performed with great economic loss and severe risk of extinction for the endangered breeds. The ability to select scrapie-resistant animals allows to define new breeding strategies aimed to boost genetic progress while reducing costs during scrapie outbreaks. Allelic variants of PRNP can be protective for caprine scrapie, and the knowledge of their distribution in goats has become very important. Over the past few years, the integration of genetic information on goat populations could be used to make selection decisions, commonly referred to as genetic selection. The objective of this review was to summarise the main findings of polymorphisms of the caprine prion protein (PrP) gene and to discuss the possible application of goat breeding schemes integrating genetic selection, with their relative advantages and limitations.